Advancing patient safety governance in the COVID-19 response - de Bienassis, Katherine (OECD Publishing, 2023)
In the backdrop of the COVID-19 pandemic, ensuring the safety of health care services remains a serious, ongoing challenge. This once-in-a-century global health crisis exposed the vulnerability of healthcare delivery systems and the subsequent risks of patient harm. Given the scale of the occurrence and costs of preventable patient safety events, intervention and investment are still relatively modest. Good patient safety governance focuses on what leaders and policy makers can do to improve system performance and reduce the financial burden of avoidable care. Moreover, it is essential in driving progress in improving safety outcomes. This report examines how patient safety governance mechanisms in OECD countries have withstood the test of COVID-19 and provides recommendations for countries in further improving patient safety governance and strengthening health system resilience
Keywords: Social Issues/Migration/Health